(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1997)
In the middle of the century the exponentially growing mankind lived according to the popular slogan of the Mitchurin - do not ask, take from the Nature everything you need. However, environmental problems we currently encounter indicate that the carrying capacity of the Earth might be soon exhausted. Our environmental consciousness has developed from the "silent spring" through the "Limits of the Growth" to the present concept of the sustainable development. If in 70-ies the main problem seemed ; to be the limitation of the resources, then now reasonable management of the Earth, the development of harpiomous existence of the manking in the Nature is in the focus. It means that much attention is paid to defining in quantitative terms what kind of management, resource Use, style 'o f life is sustainable. Long lists of quantitative parameters, Indicators of sustainability have been proposed (1, 2). Generally speaking the use of indicators should make complicated systems understandable and predictable, to show to the society, where we are, where we are going and how to intergrate different subsystems of noosphere into a sustainable wholeness. The development of adequate set of indicators is feasible only if the noosphere is described using well-founded and syncretic system of models. One of the main goals in the nearest future would probably be formulation and analysis of the hierarchical set of models of the sustainably developing Earth, models where the "climate engine" of the planet and global economy are considered as one integrated system.